Expedition Cognition: A Review and Prospective of Subterranean Neuroscience With Spaceflight Applications - Mogilever, Nicolette B.; Zuccarelli, Lucrezia; Burles, Ford; Iaria, Giuseppe; Strapazzon, Giacomo; Bessone, Loredana; Coffey, Emily B. J. (Frontiers in Human Neuroscience, 2018)
Renewed interest in human space exploration has highlighted the gaps in knowledge needed for successful long-duration missions outside low-Earth orbit. Although the technical challenges of such missions are being systematically overcome, many of the unknowns in predicting mission success depend on human behaviour and performance, knowledge of which must be either obtained through space research or extrapolated from human experience on Earth. Particularly in human neuroscience, laboratory-based research efforts are not closely connected to real environments such as human space exploration. As caves share several of the physical and psychological challenges of spaceflight, underground expeditions have recently been developed as a spaceflight analogue for astronaut training purposes, suggesting that they might also be suitable for studying aspects of behaviour and cognition that cannot be fully examined under laboratory conditions. Our objective is to foster a bi-directional exchange between cognitive neuroscientists and expedition experts by 1) describing the cave environment as a worthy space analogue for human research, 2) reviewing work conducted on human neuroscience and cognition within caves, 3) exploring the range of topics for which the unique environment may prove valuable as well as obstacles and limitations, 4) outlining technologies and methods appropriate for cave use, and 5) suggesting how researchers might establish contact with potential expedition collaborators. We believe that cave expeditions, as well as other sorts of expeditions, offer unique possibilities for cognitive neuroscience that will complement laboratory work and help to improve human performance and safety in operational environments, both on Earth and in space.